Comparative analysis of dividend payouts by national and international dividend companies for the period 2013-2019 - Jabłoński, Bartłomiej (Analiza porównawcza wypłaty dywidend przez krajowe oraz międzynarodowe spółki dywidendowe za okres 2013-2019, 2020)
The author of the article outlined the results of the research on the taxonomy and the specificity of the transfer of profits to shareholders of dividend companies which are components of the WIG, DAX, CAC40 and S&P 500 indexes for the period 2013-2019.The purpose of the article is a critical assessment of the systematic distribution of dividends by domestic and international companies, taking into account the rate of dividend growth, the cumulated rate of dividends and the average rate of return on investments in shares of these companies. The studies carried out included 120 companies listed on the Polish, German, French and American markets (30 companies in each country), which in the period 2013-2019 paid dividends and at the end of 2019 had the highest capitalization in a given index. Then the author analysed for each market only those issuers who paid the dividends without interruption during the period considered (continuously for 7 years)
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 1, s. 1-13
Keywords: dividend; dividend company; international entity; dywidenda; spółka dywidendowa; podmiot międzynarodowy